The Contribution of Emotional Intelligence to Human Resource Development and Career Success: a Review - Ana, Chagelishvili (European Journal of Economics and Business Studies, 2021)
This paper is the review of the main scientific literature about the role of emotional intelligence in career success and human resource development. It aims to analyze how emotional intelligence and its components determine human resource development or career success. Through documentary analysis the paper is based on reviewing leading scientific publications and summarizes main theoretical approaches. The results of the analyze show that emotional intelligence helps employees in many ways to achieve success at work and also highlight the need for more attention to the development of employees’ emotional intelligence in organizations. The review also addresses promotion issues which consideration will avoid organizations further problems. This analysis will be especially useful for managers to improve the quality of employees’ performance. This review on emotional intelligence issues in terms of career success contributes to review literature about human resource management and development and it may also indicate future directions for surveys.